George Nicholas Sanders family papers - Sanders, George Nicholas, 1812-1873.; Sanders, George N. (George Nicholas), 1848-1890.; Sanders, Anna Johnson Reid, approximately 1815-1890.
Correspondence, journals, and printed matter of Sanders family members relating to mid-nineteenth century politics, social life, and the Civil War. Journals of Anna Johnson Reid Sanders include notes, financial accounts, and clippings and provide information on the activities of her husband, George Nicholas Sanders; the wartime imprisonment and death of their son, Reid Sanders, a Confederate soldier; and experiences of women in the Sanders family during the Civil War. The 1863-1865 journal was begun in 1863 by George N. Sanders, Jr., while a cadet at the Virginia Military Institute. Subjects include family visits to New York City and interactions with prominent Europeans in the city; the participation of the Young America movement at the Democratic National Convention in Baltimore, Md., in 1852; the 1852 presidential election; Confederate exiles in Canada; the deaths of Henry Clay, Daniel Webster, and Franklin Pierce's son, Benjamin Pierce; and individuals such as James Buchanan, Stephen A. Douglas, John B. Floyd, and Daniel Edgar Sickles. Correspondents include G.T. Beauregard, August Belmont, J. P. Benjamin, Mary Breckinridge, Lewis Cass, Jefferson Davis, Stephen A. Douglas, John B. Floyd, Henry S. Foote, John W. Forney, R.M.T. Hunter, Stephen R. Mallory, and members of the Sanders family.
Microfilm edition of correspondence (container 2) available
Microfilm produced from originals in the Manuscript Division.
Financier, lobbyist, and Confederate agent in Europe.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Beauregard, G. T. -- 1818-1893.; Belmont, August, -- 1813-1890 -- Correspondence; Benjamin, J. P. -- 1811-1884 -- Correspondence; Breckinridge, Mary, -- 1826-1907 -- Correspondence; Buchanan, James, -- 1791-1868.; Cass, Lewis, -- 1782-1866 -- Correspondence; Clay, Henry, -- 1777-1852 -- Death and burial; Davis, Jefferson, -- 1808-1889 -- Correspondence; Douglas, Stephen A. -- 1813-1861.; Douglas, Stephen A. -- 1813-1861 -- Correspondence; Floyd, John B. -- 1806-1863.; Floyd, John B. -- 1806-1863 -- Correspondence; Forney, John W. -- 1817-1881 -- Correspondence; Hunter, R. M. T. -- 1809-1887 -- Correspondence; Mallory, Stephen R. -- 1813-1873 -- Correspondence; Pierce, Benjamin, -- 1841-1853 -- Death and burial; Sanders, Reid, -- 1837-1864.; Sickles, Daniel Edgar, -- 1819-1914.; Sanders family; Webster, Daniel, -- 1782-1852 -- Death and burial; Democratic Party (U.S.); Virginia Military Institute; American Confederate voluntary exiles -- Canada; Europeans -- New York (State) -- New York; Presidents -- United States -- Election -- 1852.; Confederate States of America -- History; New York (N.Y.) -- Social life and customs; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; United States -- Politics and government -- 19th century; Confederate agents; Financiers; Lobbyists